Initial evaluations of quercetin on the in vitro maturation of ovine oocytes - Silva, Bruna Moura (2023)
The aim of this study was to evaluate the effect of quercetin on the in vitro maturation (IVM) of oocytes and the subsequent in vitro fertilization (IVF) of ovine embryos. For this purpose, oocytes were collected and divided into the following treatment groups: control group, containing CON medium (control); and groups Q2, Q4, and Q8, with control medium supplemented with 2, 4, and 8 µM of quercetin, respectively. After IVM, the degree of cumulus cells expansion, presence of the first polar body (PB), and the other part of the oocytes proceeded to in vitro fertilization (IVF), where oocytes were incubated with spermatozoa for a period of 20 hours. Subsequently, the presumptive zygotes underwent in vitro culture (IVC) for 48 hours, and at the end of the process, the rate of cleaved structures was evaluated. The results were expressed in percentage and compared using the Chi-square test, with a significant difference considered when P<0.05. Evaluating the expansion of cumulus cells, the CON and Q2 groups showed the best expansion rates compared to the Q4 and Q8 groups. Regarding the presence of the 1st PB, it was observed that only the Q8 group exhibited lower rates compared to the control group. When evaluating the rate of cleaved structures, it was observed that the Q2 group showed a higher number compared to the Q8 group. Quercetin does not influence the maturation of ovine oocytes.